Regulatory T cells with a defect in inhibition on co-stimulation deteriorated primary biliary cholangitis - Chen, Jianing (Oncotarget, 2017)
Regulatory T cells (Tregs) play an indispensable role in the progression of primary biliary cholangitis (PBC). Although Tregs could normalize costimulation in in vivo and in vitro models, it is obscure whether and how Tregs mediate these effects in PBC. Herein we focused on the quantitative and functional characteristics of Tregs in PBC. The number and proportion of Tregs, and the production of interleukin (IL)-10 were all significantly less in the PBC patients than in the healthy controls (HCs). In addition, compared to the HCs, the costimulatory CD86 of the circulation and liver were significantly higher in the patients with PBC. CD86 expression on CD1c(+) cells negatively correlated with the proportion of Tregs. There was also a positive correlation between mayo risk score and the ratio of CD86/Treg. In vitro experiments showed that inhibition of CD86 expression on CD1c(+) cells by Tregs was significantly weakened in the PBC patients. Furthermore, the autoantibodies from the PBC patients could promote CD86 expression on CD1c(+) cells and transforming growth factor-β production by human hepatic stellate cells. Overall, Tregs declined in inhibition on co-stimulation expression in the presence of autoantibodies, which could be associated to PBC-related bile duct injury and fibrosis. This indicated that maintenance of balance of co-stimulation and Tregs could be beneficial for PBC.